The Restitution and Design Principles of Beylerbeyi Palace Gardens, Istanbul - Göker, Parisa; Erdoğan, Elmas (Journal of History Culture and Art Research, 2018)
Palaces are immovable cultural assets reflecting not only the cultural characteristics of the periods they belong to but also the lifestyles of the people who use them and the artistic understanding and techniques of the period. Beylerbeyi Palace, our research subject, is a field where western influences are clearly observed from the design of the gardens, the design features and ornaments of the buildings and spaces that form the palace. The gardens within the perimeter walls of Beylerbeyi Palace and the structures with different functions were not able to protect the original character of their design era. The purpose of this research was to scrutinize the changes that Beylerbeyi Palace gardens went through during the historical process, and to determine the changes that the location of the New Beylerbeyi Palace, the mansions in the palace complex, and the palace gardens went through during different periods in terms of their plant design characteristics, to carry out the restitution work to determine the original status by putting forward the change in the design principles, location organization, structural components and the used plant material. In conclusion, the usage characteristics of the plant and structural components of Beylerbeyi Palace gardens and the changes that they sustained during the process were determined; and the restitution work was carried out by evaluating the structural and plant components of the gardens during the period when the gardens were designed.